Perfectionism and social physique anxiety using the 2×2 model. Issue 5 (3rd September 2021) - Deck, Sarah; Roberts, Ross; Hall, Craig; Kouali, Despina
ABSTRACT: Previous research investigating the role or perfectionism in exercise has been limited by both the method of investigation and because it has largely examined the independent effects of different perfectionism dimensions as opposed to how varying within-person combinations of different aspects of perfectionism influence outcomes. Therefore, the purpose of the current study was to investigate the role of perfectionism on social physique anxiety (SPA) using the recently established 2×2 model of perfectionism. This model proposes that different forms of perfectionism, such as self-oriented (SOP) and socially prescribed perfectionism (SPP), will interact to influence different outcomes. One hundred and ninety-four college students completed a multi-section inventory comprised of demographics, the Multidimensional Perfectionism Scale (MPS; Hewitt, P. L., Flett, G. L., Turnbull-Donovan, W., & Mikail, S. F. (1991). The Multidimensional Perfectionism Scale: Reliability, validity, and psychometric properties in psychiatric samples. Psychological Assessment: A Journal of Consulting and Clinical Psychology, 3(3), 464), and the Social Physique Anxiety Scale (SPAS; Hart, Leary, & Rajeski, 1989. The measurement of social physique anxiety. Journal of Sport and Exercise Psychology, 11, 94–104. https://doi.org/10.13072/midss.598). In line with the overarching predictions of the model, we obtained a significant interaction between SOP and SPP on SPA. However, in contrast to the specific tenets of the model, the highest levels of SPA were associated with high levels of SOP and high levels of SPP ("mixed perfectionism" in the parlance of the 2×2 model). Thus, while the findings support the utility of considering within person combinations of perfectionism, they do not fully support the predictions the of the 2×2 model.